Oxylipin dynamics in dairy cows during clinical ketosis and after treatment with niacin and flunixin meglumine - Miguel Chirivi; Daniela Cortes-Beltran; Jeff Gandy; G. Andres Contreras (JDS Communications)
Dairy cows with clinical ketosis (CK) exhibit metabolic changes, including intense adipose tissue (AT) lipolysis and systemic insulin resistance, that increase plasma BHB and free fatty acids (FFA). Cows with CK also have systemic inflammation, predisposing them to inflammatory and infectious diseases. This inflammatory process is modulated in part by oxidized fatty acids (oxylipins) that regulate all aspects of inflammation. Oxylipin profiles have been characterized in healthy periparturient cows, but their dynamics during CK are unknown. Clinical ketosis is an acute metabolic disease requiring clinical therapy, commonly including propylene glycol (PG) as a gluconeogenic agent. Recently, we showed that including lipolysis inhibitors such as niacin (NIA) and flunixin meglumine (FM) improved CK recovery. These drugs may modulate oxylipin biosynthesis by regulating the release of PUFA (oxylipin substrates) and cyclooxygenase activity. However, their impact on oxylipin profiles in cows with CK is unknown. The objective of this study was to determine the dynamics of specific linoleic and arachidonic acid-derived oxylipins during CK and following therapy with PG, NIA, and FM. Multiparous Jersey cows (n = 72; 7.1 DIM) with CK from a commercial dairy were sampled. Inclusion criteria were CK symptoms (lethargy, depressed appetite, and reduced rumen fill) and blood BHB ≥ 1.2 mmol/L. The CK cows (n = 24/treatment) were randomly assigned to one of the 3 treatments: (1) PG: 310 g orally once daily for 5 d, (2) PG + NIA (PGNIA): 24 g orally once daily for 3 d, (3) PG + NIA + FM (PGNIAFM): 1.1 mg/kg i.v. once daily for 3 d. Healthy control cows (HC; n = 24) matched by lactation and DIM (±2 d) were also included. Plasma oxylipins were quantified at enrollment and 7 d later using HPLC-MS/MS. At enrollment, CK had higher concentrations of arachidonic acid (ARA)-derived 5- and 20-HETE, 8,9-, 11,12-, and 14–15-DHET, and lower concentrations of linoleic acid (LA)-derived 12,13-EpOME, 13-oxoODE, 9,10- and 12,13-DiHOME. Integrated analysis of biological pathways and oxylipin profiles using Ingenuity Pathway Analysis revealed ARA metabolism as the top pathway activated during CK. By d 7, treatment with PGNIAFM restored plasma PUFA and oxylipins to profiles similar to HC. Ingenuity Pathway Analysis showed that PGNIAFM activated the zinc transporter SLC30A7, associated with reduced activation of the ARA pathway. Results indicate that higher FA availability during CK, driven in part by dysregulated lipolysis, increases the pool of substrates for oxylipin biosynthesis. These oxylipins may play a role in both metabolic dysregulation and restoring homeostasis during CK. Inhibiting lipolysis and cyclooxygenase activity with NIA and FM can alter ARA- and LA-derived oxylipin biosynthesis. These findings underscore the potential use of lipolysis inhibitors NIA and FM in CK therapeutics and highlight the importance of understanding oxylipin pathways in the pathogenesis of CK.